Frequency of Acute Kidney Injury with Hypoxic Ischemic Encephalopathy Staging in Neonates with Perinatal Asphyxia: An Observational Study (Descriptive Case Series) - Kausar Keerio, Shazia Memon, Faiza Memon, Farah Jamil, Fiza Shah Syed (Pakistan Journal of Medical & Health Sciences, 2023)
Perinatal asphyxia affects almost all the organs in neonates, kidneys being one of commonly affected organs. Early recognition of disturbances in renal function is important for early intervention to prevent irreversible damage to kidneys. Objective: In this study we observed the frequency of acute kidney injury (AKI) in neonates with clinical staging of hypoxemic ischemic encephalopathy (HIE) in neonates with perinatal asphyxia. Methodology: An overall number of 145 term neonates with perinatal asphyxia admitted at nursery of Liaquat University Hospital, Hyderabad from February-2019 to july-2019 were included in this study. Urine output was monitored from day one and serum creatinine was sent on third day of life. Serum creatinine was sent early of those neonates having low urine output. Results: The average birth weight was 2.72±2.67 kg. There were 106 (73.1%) males and 39 (26.9%) females. Most neonates were born via simple vaginal delivery 100 (68.97%) and few via caesarian section 45 (31.03%). Out of 145 neonates 38 (26.21%) were in stage I, 95 (65.52%) in stage II and 12 (8.28%) in stage III HIE. Frequency of AKI in neonates with perinatal asphyxia was 55 (37.93%). Incidence of AKI was significantly high in stage II 45(81.8%) as compare to stage I 0(0%) and stage III 10(18.2%) (p=0.0005). Conclusion: AKI is a common complication of perinatal asphyxia. Further multicenter based and studies on large scale need to be done to identify the inter-relationship between maternal factors and perinatal asphyxia associated AKI to prevent neonatal morbidity and mortality. Keywords: Acute kidney injury, perinatal asphyxia, hypoxic ischemic encephalopathy.